2004
DOI: 10.1116/1.1768189
|View full text |Cite
|
Sign up to set email alerts
|

Interpretation of current transport properties at Ni/n–GaN Schottky interfaces

Abstract: Current transport properties at Ni/n–GaN Schottky interfaces formed on oxide-etched or thermally oxidized surfaces are studied by current–voltage–temperature (I–V–T) and capacitance–voltage measurements. The results support existence of surface patches with low Schottky barrier height (SBH), which cause a leakage current of the Schottky structures. Based on “surface patch” model, the fraction of the total patch area of 10−4–10−5 and the SBH lowering of 0.4 eV within patches are deduced for the oxide-etched Ni/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
7
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 28 publications
3
7
0
Order By: Relevance
“…As concerns the influence of thermal annealing, the annealing in O 2 led to considerable increase of the sheet carrier density, as clearly shown in Fig.1. The phenomenon seems consistent with the lowering of the effective Schottky barrier height (SBH) observed in Ni/n-(Al)GaN samples with oxidized surfaces [4]. That is, the increase of s n can be primarily explained by lowering of the surface barrier.…”
Section: Methodssupporting
confidence: 53%
See 1 more Smart Citation
“…As concerns the influence of thermal annealing, the annealing in O 2 led to considerable increase of the sheet carrier density, as clearly shown in Fig.1. The phenomenon seems consistent with the lowering of the effective Schottky barrier height (SBH) observed in Ni/n-(Al)GaN samples with oxidized surfaces [4]. That is, the increase of s n can be primarily explained by lowering of the surface barrier.…”
Section: Methodssupporting
confidence: 53%
“…Since those troublesome problems tend to become larger for E-HEMTs, influence of the surface preparation and the AlGaN thickness on electrical properties of 2DEG and Schottky gate leakage current has to be fully investigated. Previously, we have reported the influence of surface native oxides and thermal annealing on electrical properties of Ni/AlGaN/GaN heterostructures with a fixed AlGaN layer thickness [4]. In the present work, electrical properties of bare i-AlGaN/GaN and Ni/i-AlGaN/GaN Schottky samples with different surface treatments and different thickness of the AlGaN layer, which is prepared by a wet-etching process, were systematically investigated by I-V, C-V and Hall effect measurements.…”
mentioning
confidence: 99%
“…The result seems to indicate that 2DEG density is quite affected by the surface condition. Previously, we have shown that the native oxide degrades the effective SBH of Ni/n-(Al)GaN samples [6]. The decrease of the 2DEG density can be explained by the downward shift of the surface Fermi level after etching of the oxide, which enhance the electric field in the AlGaN layer and thus decrease 2DEG density.…”
Section: Resultsmentioning
confidence: 98%
“…Similar degradation has been observed for Ni/low-doped n-GaN samples, indicating the true SBH is lowered owing to the native oxide. The increased n-value can be explained by enhanced leakage current passing through surface patches with low SBH [7]. The strong bias dependence of the reverse current, which continued until pinch-off of 2DEG occurred, seems due to combination effect of tunnelling mechanism and surface patches.…”
Section: Methodsmentioning
confidence: 90%
“…For these reasons, characterizations of AlGaN/GaN systems are still necessary. Previously, we have measured electrical properties at metal/n-(Al)GaN Schottky interfaces and insulator/n-(Al)GaN interfaces formed on semiconductor single layers [7,8]. In the present work, electrical properties of Ni/i-AlGaN/GaN Schottky gate structures prepared by different surface preparation conditions were studied by I-V and C-V measurements in order to clarify the influence of surface native oxides and post-fabrication annealing in nitrogen, and the effect of insertion of a thin anodic Al 2 O 3 layer www.pss-c.com between Ni and AlGaN.…”
Section: Introductionmentioning
confidence: 99%